Analisis Kebutuhan Air Baku Masyarakat Kecamatan Singaparna Dengan Adanya Sistem Pengembangan Air Minum Instalasi Kota Kecamatan Sukarame - Ahmad Kuhunuz; Anri Noor Annisa Ramadan; Dicky Nurmayadi (JURAL RISET RUMPUN ILMU TEKNIK, 2024)
The availability of raw water is very important, both for daily needs and irrigation so that its continuity is sufficient and maintained, water needs must be planned and its use predicted. This research aims to analyze the need for Raw water in the IKK Sukarame SPAM unit for Singaparna District from 2023 to 2027 and analyze the conditions of whether the IKK Sukarame SPAM reservoir planning unit system can meet the existing water needs in Singaparna District. The method in this research is to check the availability of water from SPAM IKK Sukarame and then compare it with the water needs of Singaparna District. From the results of projection calculations based on the analysis of the maximum Raw water demand for 5 villages in Singaparna District in 2027, it is around 523,299 l/s, with an estimated need for a reservoir or storage tank of around 45,213 m³. The availability of storage tanks is around 500 m³ and cannot meet the needs of the 5 villages in Singaparna District.